Extraction of metals from nickel concentrate via FeCl3·6H2O chlorination followed by water leaching and the preparation of (Ni, Cu)Fe2O4 catalyst. (October 2022) - Zhong, Peng; Mu, Wenning; Li, Liying; Gu, Mengfei; Xin, Haixia; Lei, Xuefei; Luo, Shaohua
Graphical abstract: Highlights: The chlorination roasting was proposed to process low-grade nickel concentrate. 93.5% Ni, 90.7% Cu and 88.7% Co was synchronously extracted. The chlorination kinetics was confirmed through the thermal analysis kinetic study. Comprehensive utilization of metals is achieved by preparing NCF catalysts. Abstract: The traditional high-temperature smelting process of nickel sulfide concentrate has highlighted some problems, such as large loss of valuable metals, reduced economic benefits, and unclean production. Herein, a clean process of low-temperature chlorination roasting and water leaching was proposed to co-extract Ni, Cu and Co from low-grade nickel sulfide concentrate. The important factors such as concentrate particle size, roasting temperature, roasting time and chlorination agent dosage affecting the extraction of valuable metals were systematically studied, and 93.5 % Ni, 90.3 % Cu and 88.7 % Co were extracted under the optimal conditions. The thermal analysis kinetics of the chlorination process were investigated based on the differential thermal and thermogravimetric analysis (TG- DTA) combined with Kissinger method and Flynn-Wall-Ozawa (FWO) method. The results show that the apparent activation energy (Ea ) of the chlorination process of the metallic minerals is 65.8 kJ⋅mol −1 and the kinetic equation can be expressed as d α dt = 1.0 × 10 7 e x p - 65, 800 RT 1 - α 1.6 . The (Ni, Cu)Fe2 O4 (NCF) photocatalyst was prepared from leaching solution using α-Fe2 O3 as a carrier to composite with other valuable metals, the photocatalytic degradation rate of which to the MB solution could reach 99.7 % within 150 min. The NCF composites could retain its photocatalytic efficiency for at least four cycles of reaction under visible light irradiation.